Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.